"Csanád vármegye egyetlen szocialista sajtója" a Népköztársaság és a Vörös Hírlap a vallásról és a vallásoktatásról = "Csanád County's only socialist press" : the Népköztársaság (People's Republic) and the Vörös Hírlap (Red Gazette) on religion and religious education - Orbán Imre (Belvedere Meridionale Szeged, 2024)
The article examines how the communist newspapers in Makó wrote about religion and religious education during the time of the Hungarian Soviet Republic. It first presents the social democratic and bourgeois radical programs related to religion and religious education. Then, it analyzes the articles in the newspapers. These newspapers promoted the abolition of church schools and compulsory religious education, arguing that religion should be entirely relegated to the private sphere. Instead of compulsory religious education, the newspapers essentially advocated for the introduction of compulsory communist education. They saw the new ideal, perfect social system—communism—as the solution to all of people’s problems. The newspapers served as tools of revolutionary communist propaganda in March and April 1919 in Makó.
Keywords: Bölcsészettudományok; Történettudomány és régészet